Digital pathology with Fourier ptychography. (June 2015) - Horstmeyer, Roarke; Ou, Xiaoze; Zheng, Guoan; Willems, Phil; Yang, Changhuei
Abstract: Fourier ptychographic microscopy (FPM) is a recently introduced method of acquiring high-resolution, wide field of view (FOV) giga-pixel histology images. The FPM procedure first acquires a sequence of low-resolution images of a sample under variable-angle illumination. It then combines these images using a novel phase retrieval algorithm to improve the employed microscope's resolution beyond its conventional limit. Here, we first describe how FPM's resolution improvement can enhance wide FOV histology imaging. Second, we show that FPM also records a thin sample's optical phase, which can help pathologists digitally extract as much information as possible from a given histology slide.